To spark a match - Turano, Jen (Turano, Jen. Matchmakers (Series), 2023)
"Miss Adelaide Duveen--society misfit and confirmed spinster--is in danger of being banished from society. Former intelligence agent Gideon Abbott feels responsible for her plight and helps her relaunch into society. But when danger surrounds them and she finds herself a target of the criminals in Gideon's case, can the spark of love between them survive?"--